1982
DOI: 10.1042/bj2010367
|View full text |Cite
|
Sign up to set email alerts
|

Action of rat liver cathepsin L on collagen and other substrates.

Abstract: 1. It has been found that cathepsin L is very susceptible to loss of activity through autolysis. When this is prevented by purification and storage of the enzyme as its mercury derivative, preparations are obtained with higher specific activity than previously. 2. Active-site titration shows, however, that even the new purification method does not give preparations in which the enzyme is 100% active. 3. Benzyloxycarbonylphenylalanylarginine 7-(4-methyl)coumarylamide has been discovered to be a very sensitive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
129
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(136 citation statements)
references
References 22 publications
7
129
0
Order By: Relevance
“…The rabbit liver isoenzymes isolated in this study are chromatographically similar to rat liver cathepsin L which is also highly active against Z-PheArg-NMec [1,6]. The collagenolytic cathepsin isolated from bovine spleen, cathepsin N, has been shown to elute from CM-Sephadex at a much lower salt concentration, similar to that which elutes rabbit liver cathepsin B [2].…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…The rabbit liver isoenzymes isolated in this study are chromatographically similar to rat liver cathepsin L which is also highly active against Z-PheArg-NMec [1,6]. The collagenolytic cathepsin isolated from bovine spleen, cathepsin N, has been shown to elute from CM-Sephadex at a much lower salt concentration, similar to that which elutes rabbit liver cathepsin B [2].…”
Section: Resultssupporting
confidence: 51%
“…We have shown that the collagenolytic activity of bovine spleen was caused by cathepsin B and cathepsin N [5]. In [6], cathepsin L isolated from rat liver was also reported to degrade collagen. We have now investigated the cysteine proteinases of rabbit liver, with particular emphasis on the major sources of collagenolytic activity in this tissue.…”
Section: Introductionmentioning
confidence: 99%
“…After 5, 10 and 20 min at room temperature the same volume of 2% azocasein in 6 M urea was added and the assay was incubated 30 min at 40°C to determine the residual activity of the enzyme those of cathepsin S. The data are only valid for S from beef spleen with regard to the substrate substrate concentrations of 10 mM for Bz-Argspecificity with low-M, substrates (table 2). On the NH2 (K,,, of 3 mM has been determined for rat other hand, the same split position between Met liver cathepsin L [5]) and 10pM for Z-Phe-Argand Arg in the hexapeptide Leu-Trp-Met-Arg-PheNMec (K,,, of 7 ,uM has been determined for Val has been detected for cathepsin L from rat cathepsin L from rat [9]). …”
Section: Resultsmentioning
confidence: 57%
“…Cathepsins B and L were purified from rat liver lysosomes as in [5,9] and stored in 0.1 M acetate buffer (pH 5.0) containing 0.5 mM HgClz and 1 mM NazEDTA. Cathepsins B and S from beef spleen were purified as in [lo].…”
Section: Enzyme Preparationmentioning
confidence: 99%
“…MMPs selectively cleave collagens through a single scission across all three chains and generate about three-fourth and one-fourth length collagen fragments (5) whereas cathepsin K, similar to bacterial collagenases, cleaves type I and II collagens at multiple sites within their triple helical domains (6,7). In contrast, other cysteine proteases such as cathepsins L and B cleave collagens only in their nonhelical telopeptide regions (8).…”
mentioning
confidence: 99%